Influence of volcanic ash, rice husk ash, and solid residue of catalytic pyrolysis on the flame-retardant properties of polypropylene composites. (July 2019) - Almirón, Jonathan; Roudet, Francine; Duquesne, Sophie
This research determines whether the materials of volcanic ash (CV), rice husk ash (CR), and thermally treated solid waste (RS-T), coming from the pyrolysis of plastics, have some flame-retardant effect when added to polypropylene flame-retardant additives (such as ammonium polyphosphate and pentaerythritol). These materials were characterized by specific surface area by nitrogen adsorption analysis (Brunauer–Emmett–Teller) and X-ray fluorescence and X-ray diffraction methods. It was determined that SiO2 and Al2 O3 are considered as flame-retardant minerals. Composites composed of polypropylene, ammonium polyphosphate, pentaerythritol, and these materials at several concentrations, from 1% to 9%, were prepared. The thermal stability and flame retardancy of the composites synthesized were investigated based on the limiting oxygen index, thermogravimetric analysis, and cone calorimetry. It was determined that these materials have a synergistic action with flame-retardant additives by increasing the fireproof properties of polypropylene. Mechanical properties were determined by tensile tests.